У пошуках життєвого досвіду та мудрості (художня своєрідність казки Івана Франка «Як пан собі біди шукав») - Ворок, Х. (Слово і Час, 2021)
У статті досліджено особливості поетики твору І. Франка «Як пан
собі біди шукав». Розглянуто різні підходи до його жанрового визначення, починаючи від прижиттєвої рецепції. Відзначено наявність у
тексті виразних указівок на форму і зміст казки. Проаналізовано літературні та фольклорні джерела сюжету, біблійні алюзії, систему
персонажів, проблематику твору. Виокремлено й розглянуто художні
казкові типи юнака-чарівника та біди. Розкрито багатогранність
асоціативних зв’язків образу світла в Біблії та Франковій казці. До
аналізу залучено й інші твори письменника зі схожою проблематикою і
жанровим визначенням. The paper deals with the story “About a Nobleman Looking for а Trouble” (1887) by Ivan
Franko and highlights its genre peculiarities. The major attention is drawn to the dominant
features indicating the fairy-tale nature of the story. The literary sources of the plot, the system
of characters, biblical allusions, main issues as well as the reception of the work by contemporary
criticism have been explored. The story by Ivan Franko was based on Ukrainian
folk tales about the search for trouble performed by a nobleman or a priest.
In the field of struggle between the forces of good and evil, the images of the young
magician — Messiah — Jesus Christ and the Тrouble become the central symbols of the
tale. The Misfortune archetype, which is directly linked to Franko’s perception of the people,
suffering under circumstances of total dependence on the landlords, must be analyzed with
attention to the people’s outlook and the author’s individual thinking. The young magician
appears as Messiah, and it helps to bring a nobleman closer to something eternal and make
him reevaluate his own life. These images perform important functions in the plot and composition
of the work, revealing active changes in the character of a nobleman and forming
the philosophical and psychological discourse of the author. There is a variety of associations
between the light in the Bible and in Franko’s tale. The “light that enlightens everyone”
causes enlightenment of а nobleman. The inner state of the hero at the moment of enlightenment
is revealed in prayer. The prayer monologue demonstrates openness, sincerity, the
immediacy of self-expression and despair, and at the same time hopelessness.
The plot of the tale “About a Nobleman Looking for а Trouble” is related to Franko’s
unfinished poem “About a Richman Who Went to Buy а Trouble” (written in 1887). The
research also involves some other prose works by the writer.